Revitalizing Mobility: The Healing Power of Panchakarma in Ankylosing Spondylitis - Pavithra BJ; Swathi N; Ananta S Desai (AYUSHDHARA, 2025)
Ankylosing spondylitis (AS) is a chronic inflammatory arthritis primarily affecting the axial skeleton, commonly associated with the HLA-B27 antigen. This case report details the management of a 36-year-old male with a six-year history of low back and hip pain, diagnosed with bilateral sacroiliitis and positive HLA-B27. Conventional management with NSAIDs provided temporary relief, but symptoms persisted. The patient's presentation correlated with Amavata. Ayurvedic management focused on balancing Vata and Kapha doshas along with Ama nirharana, employing therapies such as Sarvanga Mrudu Abhyanga, Churna Pinda Sweda, churna basti and Kshara Basti. Post-treatment assessments indicated significant reductions in pain and stiffness, along with improved mobility. This case underscores the potential of Ayurvedic approaches in effectively managing ankylosing spondylitis, highlighting a holistic strategy that addresses both symptoms and underlying imbalances associated with Amavata.